Influence of substrate type and magnetic anisotropy on the spin Seebeck effect in ZnFe2O4 thin films (2023)
ABSTRACT: The longitudinal spin Seebeck effect (LSSE) has been investigated in ZnFe2O4 (ZFO) thin films on different substrates, such as Si (111), MgO (100), and SrTiO3 (100). The LSSE voltage signal exhibited a linear dependence on the temperature difference between both sides of the samples. The spin Seebeck coefficients were highly sensitive to the thermal conductivities of the magnetic layer and substrate, with values from 3 nV/k to 110 nV/K. Charge currents (Jc ) and spin currents (Js ) densities were estimated. Js values are similar for the samples deposited on MgO and STO. The saturation magnetic field for the LSSE signal was reached with a magnetic field lower than its bulk counterpart. These results were related to the lattice mismatch between the ZFO films and the substrate, the magnetic response, and the anisotropies present in the samples since a twofold in-plane anisotropy was observed for the sample deposited on Si, while the samples deposited on MgO and SrTiO3 showed a fourfold in-plane anisotropy. Moreover, the presence of a notable perpendicular magnetic anisotropy in the thin films may be a consequence of the lattice mismatch and at the same time, it can cause the saturation in the LSSE voltage hysteresis loop measured as a function of the external magnetic be reached with a low magnetic field.